(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Novel and promising macromolecular were directly synthesized by ring opening of polylactied by hydroxyl groups in cellulose diacetate as biodegradable polymers and amino acids substitution for the development of a polymeric implantable delivery carrier The remain of carboxylic groups of amino acid substitution with different drug. The toxicof the synthesized matrices were evaluated using a bacterial Staphylococcus aureuse , Micrococcus, Pseudmonasaeruginosa, klebsiella, Streptococcus. A twonew amid bond was formed between the carboxyl end-groups of the synthesized polymer matrices and an amine group ofamino acids , The structure of the polymeric conjugates was characterized by various spectroscopy techniques. A study of hydrogen nuclear magnetic resonance (1H-NMR) and differential scanning calorimetry (DSC) thermodiagrams indicated that the presence of drug pendant groups in the macromolecule structures increased the polymer’s rigidity alongside increasing thermal stability. It has been found that the kinetic release of amino acids and drugs from the obtained macromolecular conjugates, tested in vitro under different conditions, is strongly dependent on the physicochemical properties of polymeric matrices.